2015
DOI: 10.1007/s00125-015-3715-4
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance is associated with poorer verbal fluency performance in women

Abstract: Aims/hypothesis Type 2 diabetes is an independent risk factor for cognitive decline. Insulin resistance occurring during midlife may increase the risk of cognitive decline later in life. We hypothesised that insulin resistance is associated with poorer cognitive performance and that sex and APOE*E4 might modulate this association. Methods The association of insulin resistance and APOE*E4 genotype on cognitive function was evaluated in a nationwide Finnish population-based study (n = 5,935, mean age 52.5 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 52 publications
9
23
1
Order By: Relevance
“…However, baseline diabetes, hypertension, age and carriage of the APOE ε4 allele significantly modified associations between CASI and the metabolic factors. These findings suggest that metabolic risk factors for dementia may have greater effects on cognition among those with chronic metabolic diseases and among APOE ε4− individuals, which is consistent with our previous findings in trials of intranasal insulin [24], [25] and other large cohort studies [19], [26].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, baseline diabetes, hypertension, age and carriage of the APOE ε4 allele significantly modified associations between CASI and the metabolic factors. These findings suggest that metabolic risk factors for dementia may have greater effects on cognition among those with chronic metabolic diseases and among APOE ε4− individuals, which is consistent with our previous findings in trials of intranasal insulin [24], [25] and other large cohort studies [19], [26].…”
Section: Discussionsupporting
confidence: 92%
“…The results presented herein show that elevated metabolic factors and not their changes over the mid-to-late-life transition period are predictors of cognitive performance in older adults. These findings add to a growing literature relating insulin resistance and prediabetes with poorer cognitive performance in both middle-age [17], [18] and late-life [8], [9], [19], especially in those at high risk for cardiovascular disease [20]. Other studies have reported that trajectories of insulin and HbA1c are associated lower cognitive performance [21].…”
Section: Discussionsupporting
confidence: 57%
“…A weaker association was observed between HOMA-B and executive function and global cognition. Our findings are in agreement with previous studies showing similar associations of cognitive functioning with HOMA-IR in cognitively normal individuals from community-based volunteer 35 , population based 36 or family based 37 studies. Episodic memory is one of the earliest cognitive domains that show changes in the pre-clinical stages of AD.…”
Section: Discussionsupporting
confidence: 93%
“…Elevated IR is associated with increased risk of cognitive decline, including impaired verbal fluency and slow simple reaction time [16]. Therefore, the relationship between IR roles and the molecules that have a function in the brain duties in some insulin-related disorders, including prediabetes, remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%